2008
DOI: 10.1007/s00601-008-0198-6
|View full text |Cite
|
Sign up to set email alerts
|

Gerasimov-Drell-Hearn sum rule and the discrepancy between the new CLAS and SAPHIR data

Abstract: Contribution of the K + Λ channel to the Gerasimov-Drell-Hearn (GDH) sum rule has been calculated by using the models that fit the recent SAPHIR or CLAS differential cross section data. It is shown that the two data sets yield quite different contributions. Contribution of this channel to the forward spin polarizability of the proton has been also calculated. It is also shown that the inclusion of the recent CLAS C x and C z data in the fitting data base does not significantly change the result of the present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…Near the production threshold the two well established resonances S 11 (1650) and P 13 (1720) show important roles in both fits. This finding emphasizes the results of our previous studies 5, 10 . Reference 11 has also arrived at the same result, except for the P 13 (1720).…”
supporting
confidence: 92%
“…Near the production threshold the two well established resonances S 11 (1650) and P 13 (1720) show important roles in both fits. This finding emphasizes the results of our previous studies 5, 10 . Reference 11 has also arrived at the same result, except for the P 13 (1720).…”
supporting
confidence: 92%
“…In Ref. 34 it is reported that the inclusion of these data reduces the complicated structure of the total cross sections σ TT ′ as shown in the right panel of Fig. 3, which indicates that the C x and C z data select only certain important resonances, i.e.…”
Section: The Effects Of C X and C Z Datamentioning
confidence: 87%
“…In view of this, Ref. 34 proposed to use other quantities which can be predicted by the models and can be directly compared with the results from other measurements or model predictions. One of the possible quantities is the contribution of the γp → K + Λ channel to the Gerasimov-Drell-Hearn (GDH) sum rule, 35 which relates the anomalous magnetic moment of the proton κ p to the total photoabsorption cross sections σ TT ′ , i.e.…”
Section: The Problem Of Data Discrepancymentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [10] it is suggested that measurements of the polarized total cross section σ TT ′ by the CLAS, LEPS, and MAMI collaborations are expected to help to solve this problem.…”
Section: Results For Kaon Photoproductionmentioning
confidence: 99%